Development of Generic Simulation Objects in Discrete Event Simulation - Enabling Automatic Generation of Simulation Models using Process-Related Data from a PLM System - JOHANSSON , MAX; SÖDERSTRÖM, JESPER (My University, 2025)
The automotive and manufacturing industries are undergoing a transformation with the adoption of advanced simulation and data management systems. The practice of manually modeling simulation models is time-consuming and costly, which limits the feasibility of simulation studies when resources are insufficient. This master thesis thereby investigates how process-related data from a PLM system can be utilized to automatically generate generic simulation objects that accurately represent manufacturing systems. It further explores the possibilities of integration between PLM and DES applications, presenting several concepts for automatic generation and PLM/DES integration. The findings from the master thesis shows that automatic generation of generic simulation objects is achievable and effective in reducing manual efforts. Additionally, centralizing data in a single location improves input data management and enhances compatibility with different DES applications. To demonstrate this, a generic simulation tool and user-interface were developed. The solution provides improved interoperability opportunities between PLM and DES environments, reducing manual work and increasing efficiency for simulation engineers.
Keywords: Automatic Generation; Discrete Event Simulation; Generic Simulation Objects; Input Data Management; Interoperability; Product Lifecycle Management